Improvement in anaerobic germination potential and grain yield of rice (oryza sativa) through seed priming - Senapati, S; Kuanar, SR; Sarkar, RK (SAARC Journal of Agriculture, 2019)
A field experiment was conducted during the dry season of 2014 and 2015 at National Rice Research Institute (NRRI), Orissa, India, (20.5ºN, 86°E, and 23.5 meters above mean sea level). Seed priming was employed to enhance the anaerobic germination potential in two near isogenic rice lines (IR64 and IR64-Sub1). Under natural field condition, oxygen concentration in floodwater never dropped to zero. It varied from 3.0 to 5.2 mg L-1. Seed priming with calcium peroxide and seed soaking with water followed by sun drying showed greater beneficial effects as compared to potassium nitrate. Seed priming with sodium peroxide found deleterious. Cultivar IR64-Sub1 responded well due to seed priming as compared to cultivar IR64 under submergence. To improve anaerobic germination potential in rice, seed soaking with water followed by sun drying found economicalas compared to other methods of seed priming as this technique was not linked with additional investment in chemicals and was more environments friendly. SAARC J. Agri., 17(1): 37-48 (2019